2007
DOI: 10.1111/j.1651-2227.2007.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Lupin sensitization and clinical allergy in food allergic children in Norway

Abstract: Children with sensitization to lupin are not likely to have a clinical lupin allergy. Avoidance of lupin on the basis of lupin sensitization or peanut allergy would lead to unnecessarily strict diets. Food challenge is currently necessary to diagnose lupin allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…The common evolutionary origin of the 7S and 11S storage globulins in the cupin superfamily is one of the possible reasons of the observed cross-reactivity [5] and the molecular determinants responsible for their IgE-binding capacity have tentatively been identified [6]. As a matter of facts, cross-reactivities among some legume seeds, including soybean and peanut [7], soybean, lentil, pea and bean [8], lupin, pea and soybean [9], lupin and peanut [10], as well as with specific protein classes, such as pea and lentil vicilins and convicilins [11], pea and peanut vicilins [12], have been studied using various approaches. Some of these findings have recently been reviewed [13].…”
Section: Introductionmentioning
confidence: 99%
“…The common evolutionary origin of the 7S and 11S storage globulins in the cupin superfamily is one of the possible reasons of the observed cross-reactivity [5] and the molecular determinants responsible for their IgE-binding capacity have tentatively been identified [6]. As a matter of facts, cross-reactivities among some legume seeds, including soybean and peanut [7], soybean, lentil, pea and bean [8], lupin, pea and soybean [9], lupin and peanut [10], as well as with specific protein classes, such as pea and lentil vicilins and convicilins [11], pea and peanut vicilins [12], have been studied using various approaches. Some of these findings have recently been reviewed [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Hieta et al (2009), allergic reactions to lupin occurred most frequently among patients with other food allergies, mainly to legumes, indicating that lupin allergy occurs largely due to cross-reactivity. However, others showed that lupin allergy is not always due to cross-reactivity, but can be the result of primary sensitization through oral exposure (Lindvik et al, 2008;Peeters et al, 2007), and also by prior inhalation of lupin flour (Prieto et al, 2010). Similar to lupin, kiwi fruit was introduced to the EU in the 20th century and soon after kiwi allergy was first reported (Fine, 1981).…”
Section: Allergenicity Risk Assessmentmentioning
confidence: 99%
“…Additionally, sensitization and triggering of lupin allergy via inhalation (Novembre et al, 1999;Moreno-Ancillo et al, 2005;Reis et al, 2007) and by occupational exposures (Gutierrez et al, 1997;Campbell et al, 2007;Crespo et al, 2001;Parisot et al, 2001) have been described. However, lupin allergy seems to be more often the consequence of cross-reactivity in patients with existing peanut allergy (Hefle et al, 1994;Moneret-Vautrin et al, 1999;Kanny et al, 2000;Leduc et al, 2002;Faeste et al, 2004;Radcliffe et al, 2005;Guarneri et al, 2005;Wassenberg and Hofer, 2007;Lindvik et al, 2008, Shaw et al, 2008.…”
Section: Routes Of Exposurementioning
confidence: 99%
“…Existing data from some studies involving primarily lupin-sensitized and cross-reacting peanut allergic patients indicate that eliciting doses for objective symptoms might be in the range from 265 to 1000 mg of lupin protein (Moneret-Vautrin et al, 1999;Kanny et al, 2000;Peeters et al, 2007;Lindvik et al, 2008). The eliciting dose for subjective oral allergy syndromes was only 1 mg or less (Peeters et al, 2007).…”
Section: Threshold Dosesmentioning
confidence: 99%
See 1 more Smart Citation